1996
DOI: 10.1074/jbc.271.3.1314
|View full text |Cite
|
Sign up to set email alerts
|

Folding-related Dimerization of Human Cystatin C

Abstract: With the aim to improve our understanding of the structural basis for protein self-association and aggregation, in particular in relationship to protein refolding and amyloid formation, folding-related processes for human cystatin C have been studied. Using NMR spectroscopy together with chromatographic and electrophoretic methods, a self-association process resulting in dimer formation for protein samples treated with denaturing agents as well as for samples subjected to low pH or high temperature conditions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

16
102
0
1

Year Published

1997
1997
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(119 citation statements)
references
References 40 publications
(34 reference statements)
16
102
0
1
Order By: Relevance
“…L68Q cystatin C, the cystatin C variant causing hereditary cystatin C amyloid angiopathy, has an increased propensity to form dimers compared with that of wt cystatin C, since the mutation lowers the energy barrier for the transition through destabilization of the monomeric structure and stabilization of the unfolded intermediate (22). However, also wt cystatin C has been shown to dimerize in vitro and the rate of the process could be increased by raising the temperature, lowering the pH, or using conditions of mild chemical denaturation (40). Transformation of monomeric wt cystatin C into amyloid fibrils in vitro has also been described, but the system used required a very low pH of 2.0 and did not allow detection of any molecular intermediates of the transformation (28).…”
Section: Discussionmentioning
confidence: 99%
“…L68Q cystatin C, the cystatin C variant causing hereditary cystatin C amyloid angiopathy, has an increased propensity to form dimers compared with that of wt cystatin C, since the mutation lowers the energy barrier for the transition through destabilization of the monomeric structure and stabilization of the unfolded intermediate (22). However, also wt cystatin C has been shown to dimerize in vitro and the rate of the process could be increased by raising the temperature, lowering the pH, or using conditions of mild chemical denaturation (40). Transformation of monomeric wt cystatin C into amyloid fibrils in vitro has also been described, but the system used required a very low pH of 2.0 and did not allow detection of any molecular intermediates of the transformation (28).…”
Section: Discussionmentioning
confidence: 99%
“…It was previously shown that recombinant normal cystatin C dimerizes when exposed to denaturing agents, low pH, or high temperature (43). Although these conditions are similar to those leading to protein unfolding, it was demonstrated that cystatin C dimers are formed by association of native, properly folded proteins (43).…”
Section: Source Of Proteasementioning
confidence: 99%
“…Although these conditions are similar to those leading to protein unfolding, it was demonstrated that cystatin C dimers are formed by association of native, properly folded proteins (43). The dimers and aggregates of the variant recombinant protein were formed at normal body temperature, nearly 25°C lower than that needed for the wild type cystatin C dimerization (25).…”
Section: Source Of Proteasementioning
confidence: 99%
See 1 more Smart Citation
“…The mechanisms controlling the intracellular inhibition of cysteine proteinases in endosomes and lysosomes with cystatin C entering the endosomal -lysosomal pathway by endocytotic uptake may include dimerisation (Ekiel and Abrahamson, 1996;Merz et al, 1997), proteolytic fragmentation by cathepsin D (Lenarčič et al, 1991) or neutrophilic granulocyte elastase (Abrahamson et al, 1991). Some of these mechanisms may operate already in the pericellular microenvironment and may restrict the inhibitory function of the secreted cystatin C against the proteolytic activity of cell surface associated and/or secreted enzymes (Křepela et al, 1998).…”
mentioning
confidence: 99%